2006
DOI: 10.1681/asn.2005101119
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical Dimethylarginine

Abstract: Symmetrical dimethylarginine (SDMA) is the structural isomer of the endogenous nitric oxide synthase (NOS) inhibitor asymmetric dimethylarginine. Whereas the major route of asymmetric dimethylarginine elimination is the hydrolytic degradation by dimethylarginine dimethylaminohydrolase, SDMA is eliminated by renal excretion. SDMA does not directly inhibit NOS but is a competitor of arginine transport. This study showed for the first time that measurement of SDMA can be a marker of estimated GFR and extent of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
204
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(223 citation statements)
references
References 43 publications
14
204
0
1
Order By: Relevance
“…Endothelial dysfunction and hypertension are common features of advanced CKD and major contributing factors to the pathogenesis of CVD in this population. These abnormalities in part result from a deficiency of nitric oxide, which is caused by downregulation of eNOS, an accumulation of the eNOS inhibitor, asymmetrical dimethylarginine, and ROS-mediated degradation of nitric oxide 103 . A number of studies have revealed the presence of large amounts of symmetrical dimethyl arginine (SDMA) -which blocks the uptake of L-arginine by endothelial cells -in HDL from patients with advanced CKD 104 .…”
Section: Progression Of Ckdmentioning
confidence: 99%
“…Endothelial dysfunction and hypertension are common features of advanced CKD and major contributing factors to the pathogenesis of CVD in this population. These abnormalities in part result from a deficiency of nitric oxide, which is caused by downregulation of eNOS, an accumulation of the eNOS inhibitor, asymmetrical dimethylarginine, and ROS-mediated degradation of nitric oxide 103 . A number of studies have revealed the presence of large amounts of symmetrical dimethyl arginine (SDMA) -which blocks the uptake of L-arginine by endothelial cells -in HDL from patients with advanced CKD 104 .…”
Section: Progression Of Ckdmentioning
confidence: 99%
“…Western blotting was performed as described recently, 25 with some modifications. Total cellular protein was measured using a BCA protein assay kit (Pierce).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…With regards to SDMA, it has been demonstrated that it is a strong determinant of both GFR and the extent of coronary atherosclerosis in patients with ischemic heart disease and mild to moderate chronic kidney disease [16]. The fact that renal function is an important determinant for SDMA concentrations is not new, since urinary excretion is generally accepted as a SDMA modulating process.…”
Section: Discussionmentioning
confidence: 99%
“…SDMA was initially considered an inactive isomer of ADMA, when it was shown to correlate with the glomerular filtration rate [15]; nowadays SDMA is considered a marker of GFR and a marker of the extent of coronary artery disease [16].…”
Section: Introductionmentioning
confidence: 99%